Medical treatment of superficial thrombophlebitis of the lower limb: Heparin or anti-inflammatory drugs? - Botas, Philippe (2012)
Objectives: The objective of this review is to compare treatment with non-steroidal anti-inflammatory drugs (NSAID) and low- molecular-weight heparin (LMWH) for superficial thrombophlebitis (ST) of the lower limb. Data sources: We searched the PubMed database, evidence-based medicine websites, the General Directorate of Health websi- te, the Portuguese Association of General Practitioners website, MGFamiliar.net, and the Index of Portuguese Medical Magazines. Review methods: We selected clinical guidelines (CG), computerized decision support systems (CS), systematic reviews (SR) and original studies, published between January 2008 and May 2011, using the MeSH terms venous thrombosis, heparin, low molecular weight, and anti-inflammatory agents. American Family Physician's Strength of Recommendation Taxonomy (SORT) was used to assess the level of evidence. Results: 215 articles were obtained. We selected one CG, one CS, one SR and one randomized clinical trial (RCT) for this review. The evidence found suggests that LMWH or NSAIDs are superior to placebo in the treatment of symptoms of ST, and in redu- cing the incidence of recurrences and complications, without differences in their safety profile in the short term (level of evi- dence 2). The evidence also confirms anticoagulation as the first line of therapy (level of evidence 2). The simultaneous use of LMWH and NSAID was found to be more effective for symptomatic relief than LMWH alone in one RCT (level of evidence 2). Conclusions: There is evidence for the use of LMWH and NSAID as first-line treatment for ST (SOR B). Anticoagulation for at least 4 weeks is indicated especially when the following criteria are present: anatomical proximity of the thrombus to the deep venous system and medical risk factors for deep vein thrombosis (SOR B). More randomized clinical trials are needed, comparing LMWH and NSAID, evaluating the simultaneous use of these drugs, and assessing the proper dose and duration of treatment.